Pandangan Filsafat Progresivisme Terhadap Implementasi Pembelajaran Diferensiasi Dalam Mata Pelajaran IPAS - Sri Kasih; Budiyanto; Agus Darmuki; Mohammad Kanzunnudin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This research discusses John Dewey's views on progressivism and differentiated learning, as well as the implementation of differentiated learning in the IPAS subject in elementary schools. This study uses a literature review method by referring to relevant books and scientific journals. This research produces meaningful information about the relationship between progressivism and differentiated learning, as well as the benefits of differentiated learning in the IPAS subject. The study concludes that progressivism is an educational perspective that supports a student-oriented education process and learning that continues to evolve with the times. Differentiated learning is learning that is tailored to the learning needs of students, based on their readiness to learn, learning profiles, interests, and talents. Differentiated learning can be carried out in several ways, including: content differentiation, process differentiation, product differentiation, and learning environment differentiation. Differentiated learning in the subject of IPAS can help students develop scientific, creative, and critical thinking skills in understanding concepts, phenomena, and issues related to nature. Differentiated learning in the IPAS subject can also facilitate students to explore, discover, and apply IPAS knowledge according to their interests and talents.